Factors That Influence the Health Seeking Behavior and Degree of Health Service Utilization of Ethiopian Immigrants Living in One of the Midwest Cities of the United States: A Mixed Methods - (:unkn) unknown (My University, 2021)
ABSTRACTFACTORS THAT INFLUENCE THE HEALTH SEEKING BEHAVIOR AND DEGREE OF HEALTH SERVICE UTILIZATION OF ETHIOPIAN IMMIGRANTS LIVING IN ONE OF THE MIDWEST CITIES OF THE UNITED STATES: A MIXED METHODS Immigrants have a significantly higher prevalence of chronic diseases, such as diabetes, hypertension, heart disease, and worse health outcomes than native-born individuals in the United States. The disproportionate adverse outcomes have been associated with structural, systemic, and socioeconomic inequalities and individuals’ Health-Seeking Behavior (HSB) and patters of Health Service Utilization (HSU). The purpose of this study was twofold. First, the survey explored (a) factors influencing the HSB of Ethiopian immigrants and the extent of HSU, (b) the relationship of predisposing and enabling factors related to HSU. Secondly, the study examined the role of religious and community leaders in influencing the HSB of their members. The study used a combined conceptual framework adapted from Andersen Behavioral Health and Health Belief Models. This cross-sectional, parallel convergent, community-based mixed-method study employed survey questions to collect data on HSB, access, and HSU, and a seven Focus Group Discussions (FGDs) of faith and community leaders. The result demonstrated that lack of insurance coverage (p=.009), immigration status (p=.005), English language proficiency (p=.045), and acculturation (p
Keywords: Acculturation; English Language Proficiency; Ethiopian immigrants; Health Behavior; Immigrant Health; Length of Stay in the United States